Helicobacter pylori modulates cyclooxygenase-2 and 15-hydroxy prostaglandin dehydrogenase in gastric cancer - Zhao, Jianqiu (Oncol Lett, 2017)
Persistent infection with Helicobacter pylori may contribute to the carcinogenesis of gastric cancer through modulating local prostaglandin E(2) (PGE(2)) levels. Cyclooxygenase-2 (COX-2) and 15-hydroxy prostaglandin dehydrogenase (15-PGDH) are two key enzymes that regulate PGE(2) synthesis and inactivation, respectively. The present study was designed to investigate the expression of COX-2 and 15-PGDH in gastric cancer specimens (n=66) in comparison to that of control specimens (n=70) and, furthermore, to semi-quantitatively assess the level of COX-2 and 15-PGDH mRNA and protein in tissues with or without H. pylori infection by reverse transcription-polymerase chain reaction and immunohistochemistry, respectively. It was revealed that COX-2 was expressed in almost all gastric cancer specimens infected with H. pylori (32 out of 33 specimens), but it was also expressed in 2/3 gastric cancers without H. pylori infection (22 out of 33 specimens). By contrast, COX-2 was expressed in <1/6 control subjects regardless of H. pylori infection. Furthermore, 15-PGDH was expressed in control samples but significantly downregulated in gastric cancer specimens. H. pylori infection resulted in slight inhibition of 15-PGDH in control subjects, but significant inhibition of 15-PGDH mRNA expression and protein synthesis in the gastric cancer specimens. These findings indicated that COX-2 and 15-PGDH, the two enzymes that regulate PGE(2) levels, were significantly altered in gastric cancer, and that H. pylori may contribute to gastric carcinogenesis through modulating COX-2 and 15-PGDH mRNA expression and protein synthesis.